Increase in Short Interest and Predictability in Stock Returns (Infiniti 2011) - Mohamad, Azhar; Aziz, Jaafar; Hodgkinson, Lynn; Wells, Jo (2011)
This paper, following Diamond and Verrecchia (1987) and Senchack and Starks (1993) questions whether significant negative stock returns follow increases in short interest using a more recent and comprehensive dataset from the UK. In addition, the paper also questions whether increasing levels of short interest lead to increasingly negative returns. Using the UK daily short interest data from the period of September 2003 to April 2010, we find a significant negative relation between increases in short interest and subsequent returns on equal-weighted basis. The results indicate informational content of increases in short interest which is consistent with Diamond and Verrecchia (1987) hypotheses.